Beyond financial repression and regulatory capture: the recomposition of European financial ecosystems after the crisis - Eric Monnet; Stefano Pagliari; Shahin Vallée (London School of Economics and Political Science (LSE), European Institute, 2019)
The financial crisis has radically changed the political economy of the European financial system. The evolution of relations between European states and their respective financial systems has given rise to two competing narratives. On the one hand, government agencies are often described as being at the mercy of the financial sector, regularly hijacking political, regulatory and supervisory processes. This trend is often referred to as "regulatory capture" and would explain the "soft touch" regulation and bank bailout. On the other hand, governments are portrayed as subverting markets and abusing the financial system for their benefit, mainly to obtain better financing conditions and allocate credit to the economy on preferential terms, a trend called "financial repression" that is considered corrosive to the proper functioning of free markets and a source of capital misallocation. This paper takes a critical look at this debate and argues that the relationship between governments and financial systems in Europe cannot be reduced to the polar notions of "capture" and "repression", but that the channels of pressure and influence between governments and their financial systems have often been bi-directional and mutually reinforcing.
Keywords: 330; European financial systems; Financial repression; Regulatory capture